Estudo de padrões alimentares com foco em características socioeconômicas e demográficas em adultos do sul do Brasil - Canuto, Raquel (Universidade do Vale do Rio do Sinos, 2009)
Introduction: The aim of the present article is to introduce Focused Principal Component Analysis (FPCA) as a novel exploratory method for providing insight into dietary patterns that emerge based on a given characteristic of the sample. Methods: To exemplify the use of FPCA, we used the database of a survey of a representative sample of 1,968 adults living in the city of Pelotas, Southern Brazil. Food intake was obtained using an intake frequency questionnaire (IFQ) covering 26 food items. The population variables – termed focus variables in FPCA – used for analysis were age, income, and schooling. All analyses were carried out using R software (R Development Core Team, 2009). Results: The graphs generated show evidence of socioeconomic inequities in the dietary patterns of adults. Intake of whole foods, fruit, and vegetables was positively correlated with income, whereas for refined cereals, animal fats (lard), and white bread this correlation was negative. When the focus variable was schooling, the graph
Keywords: análise de componentes principais focada; escolaridade; renda; padrões alimentares; dietary patterns; education; income; focused principal component analysis; Ciências da Saúde